A CLASS CONFLICT AS REFLECTED IN THE HUNGER GAMES BY GARY ROSS - Sherly Dwi Marlina; Yosep Bambang Margono (LINGUAMEDIA Journal, 2022)
ABSTRACTClass conflict occurs because of the relationship between one class and another. In this thesis, I analyze the class conflict that occurs in The Hunger Games the film by Gary Ross (2012). The class conflict that occurs in this film is the difference in social life between the upper and lower classes represented by the citizens of the Capitol and the Districts. In this thesis I emphasize on the existence of class distinctions that cause class conflicts. I used a qualitative descriptive method by analyzing scripts and scenes that contain the main topic in the film. I used theory about literature and film to prove that film is a literary work as well as literature and society theory as well as a mimetic approach as a literature approach. In relation to the main topic, I also used the theory about class conflicts. As a result of this analysis, I found that there is a class division between the Capitol and the Districts which is class conflict in both classes because of their interaction. I concluded that the problems that exist between these two classes depend on power and economy. Keywords: Class Conflict, Game, Film, Society, Literature.